Analysis of Logistics Technology, Logistics Infrastructure and Quality of logistics services on E-Commerce Growth - Tohir, Muhammad; Primadi, Andri; Dzulqa Indah, Desy (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The Influence of Logistics Technology, Logistics Infrastructure, and Logistics Service Quality on E-commerce Growth is a scientific literature review article within the scope of the field of study. The purpose is to identify factors influencing online sales in the e-commerce sector in Indonesia, such as gender and income. The secondary data used in this paper is obtained from the kaggle.com web platform, which provides various datasets relevant to various topics. The results of this article show: 1) Logistics Technology influences E-commerce Growth; 2) Logistics Infrastructure influences E-commerce Growth; and 3) Logistics Service Quality influences E-commerce Growth.